Pertanggungjawaban Pidana Dalam Tindak Pidana Penyeludupan Ballpress Di Wilayah Perairan Selat Malaka Di Sumatera Utara - Windianto Windianto; Ediwarman Ediwarman; Muhammad Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to examine and analyze the legal rules governing the criminal act of ballpress smuggling, and how the factors that cause ballpress smuggling in the waters of the Malacca Strait in North Sumatra, and how the policies are taken against ballpress smuggling in the waters of the Malacca Strait in Sumatra. North. The problem is focused on how the laws governing the criminal act of ballpress smuggling and the factors causing ballpress smuggling as well as the policies implemented in handling the crime of ballpress smuggling. The research method in this paper is a normative legal research method. The data were collected through primary, secondary and tertiary data sources, then analyzed using qualitative analysis methods. This study concludes that the legal rules regarding the criminal act of ballpress smuggling are as follows: (a) Law Number 17 of 2006 concerning Amendments to Law no. 10 of 1995 concerning Customs. (b) Law Number 8 of 1999 concerning Consumer Protection (UUPK) (c) Regulation of the Minister of Trade of the Republic of Indonesia Number 51/M-DAG/PER/7/2015 of 2015 concerning the Prohibition of the Import of Used Clothing (d) Decree of the Minister of Industry and Trade No.732/MPP/Kep/10/2002 concerning Textile Import Trading System. The factors causing ballpress smuggling in the waters of the Malacca Strait in North Sumatra are: (a) Geographical Factors, (b) Domestic Industry Conditions. (c), Natural Resources (SDA), (d) Excess Production, (e) Transportation, (f) Mentality, (g) Society. The policies taken against ballpress smuggling in the waters of the Malacca Strait in North Sumatra are: (a) The penal route, namely by applying criminal law (criminal law application), (b) The non-penal route.